ASSESSING LONTARAQ WRITING COMPETENCE THROUGH SYSTEMIC FUNCTIONAL LINGUISTICS: EVALUATING NARRATIVE DEVELOPMENT AND TEXTUAL ORGANIZATION - Andi Fatimah Junus; Andi Sahtiani Jahrir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates the Lontaraq writing competence of pre-service Bugis language teachers by applying a Systemic Functional Linguistics (SFL) framework to evaluate their narrative development and textual organization. Thirteen handwritten Lontaraq narrative texts produced in the Marukiq course served as the primary data. Using a qualitative descriptive design, the analysis examined genre structure, ideational choices, theme–rheme patterns, and cohesive devices. The findings reveal strong and consistent control of Orientation and Sequence of Events, driven by action-based clauses dominated by material processes (63–74%), reflecting the influence of oral storytelling traditions. However, Complication and Coda were infrequently realized, showing limited ability to construct tension, evaluation, and reflective closure. Textual organization was characterized by locative topical themes, constant thematic progression, and simple additive cohesion, with minimal reference chains or complex logical connectors. These patterns indicate that students are transitioning from oral to written narrative conventions but have not yet developed advanced textual management. The study highlights a need for explicit SFL-based instruction in narrative staging, ideational diversification, and theme–rheme structuring to strengthen Lontaraq literacy. The findings contribute to the emerging scholarship on indigenous script revitalization by demonstrating how SFL can be applied to assess and enhance writing competence in non-Latin, heritage-script contexts.